2017
DOI: 10.1038/srep45964
|View full text |Cite
|
Sign up to set email alerts
|

p38α MAPK regulates proliferation and differentiation of osteoclast progenitors and bone remodeling in an aging-dependent manner

Abstract: Bone mass is determined by the balance between bone formation, carried out by mesenchymal stem cell-derived osteoblasts, and bone resorption, carried out by monocyte-derived osteoclasts. Here we investigated the potential roles of p38 MAPKs, which are activated by growth factors and cytokines including RANKL and BMPs, in osteoclastogenesis and bone resorption by ablating p38α MAPK in LysM+monocytes. p38α deficiency promoted monocyte proliferation but regulated monocyte osteoclastic differentiation in a cell-de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
61
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(63 citation statements)
references
References 58 publications
(73 reference statements)
1
61
1
Order By: Relevance
“…Reports have also indicated that the p38MAPK-dependent signaling pathway enhances Col-I synthesis and bone mineralization in rats [48]. p38MAPK signaling pathway is involved in osteoblast proliferation and differentiation, and plays important roles during osteogenic differentiation [49,50]. Based on these studies, we speculate EPCs induce osteogenic differentiation in co-cultured mesenchymal stem cells via the p38MAPK signaling pathway.…”
Section: Discussionmentioning
confidence: 57%
“…Reports have also indicated that the p38MAPK-dependent signaling pathway enhances Col-I synthesis and bone mineralization in rats [48]. p38MAPK signaling pathway is involved in osteoblast proliferation and differentiation, and plays important roles during osteogenic differentiation [49,50]. Based on these studies, we speculate EPCs induce osteogenic differentiation in co-cultured mesenchymal stem cells via the p38MAPK signaling pathway.…”
Section: Discussionmentioning
confidence: 57%
“…Indeed, a previous study showed that both p38a and p38b knock-out mice exhibited lower bone mass compared with wild-type mice, although this phenotype was mainly affected by osteoblast activity (33). Intriguingly, p38a conditional knockout mice in OCs exhibited distinct alterations in bone resorption at 2.5 and 6 mo of age, and p38a can positively or negatively regulate osteoclastogenesis in different cultural conditions in vitro (34). In reality, there are limited studies showing the role of p38 in the selective inhibition on osteoclastogenesis (35,36).…”
Section: Discussionmentioning
confidence: 96%
“…p38 MAPK is a member of MAPK family that has an important role in tissue development and homeostasis functions such as cell differentiation, apoptosis, maturation, and cytokine production which initiates osteoclastogenesis. (8,9) After being activated, p38 MAPK will induce important transcription factors such as NFkB and NFATc1. (8,9,12) Inhibition of p38 MAPK was reported to fully diminish RANKL and TNF-α-induced osteoclast formation.…”
Section: Discussionmentioning
confidence: 99%
“…(8,9) After being activated, p38 MAPK will induce important transcription factors such as NFkB and NFATc1. (8,9,12) Inhibition of p38 MAPK was reported to fully diminish RANKL and TNF-α-induced osteoclast formation. (15) In the present study, RANKL and TNF-α induced formation of TRAP + PNCs, meanwhile pretreatment of caffeic acid could diminish the formation of RANKL and TNF-α-induced TRAP + PNCs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation